2007
DOI: 10.1681/asn.2006090973
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasm Antibody–Stimulated Neutrophil Adhesion Depends on Diacylglycerol Kinase–Catalyzed Phosphatidic Acid Formation

Abstract: Patients with certain forms of systematic vasculitis, such as Wegener's granulomatosis, have circulating antineutrophil cytoplasmic antibodies (ANCA). These inappropriately stimulate circulating neutrophils adhere to and thereby obstruct small vessels. This, together with ANCA-induced degranulation and an oxidative burst, leads to local tissue damage. The signaling pathways that are activated by ANCA IgG are distinct from those that are involved in normal neutrophil activation. This study shows that diacylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…IgG was purified from patient PEX fluid and healthy control serum by protein G affinity chromatography (GE Healthcare, Buckinghamshire, UK) and eluted with 0.1 M glycine (pH 2.7). 38 Concentrations were determined by spectrophotometry. IgG samples were purified at the time of conducting this study, and results of the original ANCA testing were verified by retesting derived IgG samples in the Clinical Laboratory.…”
Section: Uk Cohortmentioning
confidence: 99%
“…IgG was purified from patient PEX fluid and healthy control serum by protein G affinity chromatography (GE Healthcare, Buckinghamshire, UK) and eluted with 0.1 M glycine (pH 2.7). 38 Concentrations were determined by spectrophotometry. IgG samples were purified at the time of conducting this study, and results of the original ANCA testing were verified by retesting derived IgG samples in the Clinical Laboratory.…”
Section: Uk Cohortmentioning
confidence: 99%
“…We previously reported that ANCA IgG induces neutrophil adhesion through a pathway involving DGKcatalyzed monounsaturated or saturated PA formation, although this pathway is not used for ANCA-mediated superoxide release (13). In this study, we now report that ANCA-induced DGK-mediated formation of PA promotes exocytosis of the azurophilic granules by dual effects on calcium and membrane fusion.…”
Section: Discussionmentioning
confidence: 69%
“…Exocytosis was also measured after neutrophil adhesion. Neutrophils (2.5 × 10 6 /mL) were primed with TNF-α (2 ng/mL) in the absence of cytochalasin B for 15 min and stimulated in 96-well flat-bottom plates previously coated with fibrinogen (25 μg/mL) as described previously (13). After 2 h of treatment, supernatants were removed and spun down to remove any unbound neutrophils and MPO release was measured as above.…”
Section: Exocytosis Assaymentioning
confidence: 99%
See 2 more Smart Citations